The Lisbon Agreement on Femoroacetabular Impingement Imaging—part 3: imaging techniques - Castro, Miguel O.; Mascarenhas, Vasco V.; Afonso, P. Diana; Rego, Paulo; Schmaranzer, Florian; Sutter, Reto; Kassarjian, Ara; Sconfienza, Luca; Dienst, Michael; Ayeni, Olufemi R.; Beaulé, Paul E.; Dantas, Pedro; et al. (European radiology, 2021)
Objectives Imaging diagnosis of femoroacetabular impingement (FAI) remains controversial due to a lack of high-level evidence, leading to significant variability in patient management. Optimizing protocols and technical details is essential in FAI imaging, although challenging in clinical practice. The purpose of this agreement is to establish expert-based statements on FAI imaging, using formal consensus techniques driven by relevant literature review. Recommendations on the selection and use of imaging techniques for FAI assessment, as well as guidance on relevant radiographic and MRI classifications, are provided. Methods The Delphi method was used to assess agreement and derive consensus among 30 panel members (musculoskeletal radiologists and orthopedic surgeons). Forty-four questions were agreed on and classified into five major topics and recent relevant literature was circulated, in order to produce answering statements. The level of evidence was assessed for all statements and panel members scored their level of agreement with each statement during 4 Delphi rounds. Either “group consensus,” “group agreement,” or “no agreement” was achieved. Results Forty-seven statements were generated and group consensus was reached for 45. Twenty-two statements pertaining to “Imaging techniques” were generated. Eight statements on “Radiographic assessment” and 12 statements on “MRI evaluation” gained consensus. No agreement was reached for the 2 “Ultrasound” related statements. Conclusion The first international consensus on FAI imaging was developed. Researchers and clinicians working with FAI and hip-related pain may use these recommendations to guide, develop, and implement comprehensive, evidence-based imaging protocols and classifications. Key Points • Radiographic evaluation is recommended for the initial assessment of FAI, while MRI with a dedicated protocol is the gold standard imaging technique for the comprehensive evaluation of this condition. • The MRI protocol for FAI evaluation should include unilateral small FOV with radial imaging, femoral torsion assessment, and a fluid sensitive sequence covering the whole pelvis. • The definite role of other imaging methods in FAI, such as ultrasound or CT, is still not well defined.